DESAIN DIDAKTIS PENYAJIAN DATA STATISTIK KELAS V SEKOLAH DASAR - INGGRIT GANTINA, - (2020)
The research aims to design a didactic design of the learning obstacle analysis in learning concept of statistical data presentation in 5th grade of Pakuwon I Elementary School, Sumedang Selatan District, Sumedang Regency. The design is important because the concept of presenting data is the basis for students to develop an understanding of other mathematical material, one of the prerequisite skills of some material to be taught. The important aspect that becomes the focus of research is about the concept of learning the presentation of statistical data, potential learning obstacle that might occur, and proposing a learning design that can minimize the potential of the learning obstacle. The method is the qualitative method of the Didactical Design Research (DDR) model through the prospective analysis as a single analysis method. Data was collected with triangulation techniques in the form of documentation studies, written tests, and interviews. Based on the research findings, revealed that there are five types of learning difficulties experienced by students on the concept of statistical data presentation that is classified in the category of ontogenesis obstacle, didactical obstacles, and epistemological obstacle. In addition, based on the results of learning obstacle analysis and learning theory designed a didactical design to minimize learning obstacles.